2017
DOI: 10.1080/08982104.2017.1391285
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic preparation of drug-loaded PEGylated liposomes, and the impact of liposome size on tumour retention and penetration

Abstract: Understanding the effect of liposome size on tendency for accumulation in tumour tissue requires preparation of defined populations of different sized particles. However, controlling the size distributions without changing the lipid composition is difficult, and differences in compositions itself modify distribution behaviour. Here, a commercial microfluidic format as well as traditional methods was used to prepare doxorubicin-loaded liposomes of different size distributions but with the same lipid composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Successful formulation of safe, stable and efficient nanocarriers, therefore, requires the preparation of homogenous (monodisperse) populations of nanocarriers of a certain size. However, it is difficult to control the particle size distribution without considering the composition of the nanocarriers and the nature of the solvents and co-solvents used during their preparation [ 8 , 75 , 76 ]. Following preparation, nanocarriers must be characterized to assure their suitability for in vitro and in vivo applications.…”
Section: Polydispersity Indexmentioning
confidence: 99%
“…Successful formulation of safe, stable and efficient nanocarriers, therefore, requires the preparation of homogenous (monodisperse) populations of nanocarriers of a certain size. However, it is difficult to control the particle size distribution without considering the composition of the nanocarriers and the nature of the solvents and co-solvents used during their preparation [ 8 , 75 , 76 ]. Following preparation, nanocarriers must be characterized to assure their suitability for in vitro and in vivo applications.…”
Section: Polydispersity Indexmentioning
confidence: 99%
“…This can be achieved in a single process without the need for postprocessing or changing the lipid composition of the liposomes 30,35 . Cancer therapy is one example where size reduction of liposomes is desirable 34 . A recent study by Dong et al demonstrated that by using MF methodology it was possible to reduce the size of doxorubicin-loaded liposomes to 50 nm.…”
Section: Fabrication and Physicochemical Characterization Of L-aunp Hmentioning
confidence: 99%
“…Furthermore, this control is achieved in a single step without the need for additional post-production processing through extrusion or sonication. Very promising examples of liposomal systems with high payload capacity of hydrophilic and/or lipophilic drugs have been reported 34,35,36,37,38 . Moreover, advances in the design of integrated microfluidic devices allow the combination of in-line liposome fabrication with other processes such as remote drug loading 39 , and complexation with genetic material such as pDNA and siRNA 40 .…”
Section: Introductionmentioning
confidence: 99%
“…PEG-coated particles are known as long circulating lipid particles and have longer half-lives compared to conventional or targeted LNPs. 42 Blood samples collected 24 hours post-administration also confirmed the total clearance of non-targeted PEG-LNP(Cal), PEG-LNP(Cal)-IgG, and PEG-LNP(Cal)-αmCD163 in blood, comparable to the control PBS mice group (not shown). At 25 hours post-LNP administration, ex vivo imaging of the organs confirmed the accumulation of PEG-LNP(Cal) only in the liver, in contrast to the accumulation of PEG-LNP(Cal)-αmCD163 in the liver and spleen.…”
Section: Effects Of Encapsulated Calcitriol On Proinflammatory Cytokimentioning
confidence: 57%